Literature Study: Application of Self Assessment in Improving Character Quality, 21st Century Abilities, and Physics Learning Results - Dhea Febriya; Festiyed; Nur Hikmah; Fatni Mufit (Postgraduate, University of Mataram, 2023)
This study aims to examine the literature related to the application of self-assessment in improving character quality, 21st century abilities, and physics learning outcomes. The method used is library research or literature study by collecting international and national articles over a 10 year range (2013-2022). This research begins by analyzing appropriate assessment in 21st century education and its real application in the education sector. The research results show that the implementation of self-assessment is not yet comprehensive in every school and level of education. High school in grade X is a school that often implements self-assessment in learning physics. However, self-assessment does not only play a role in improving physics learning outcomes, but also improving the quality of student character, Higher Order Thinking Skills (HOTS), scientific attitudes, knowledge and (intellectual) skills, student attitudes, critical thinking skills in scientific literacy, TPACK for prospective physics teachers, students' scientific literacy, students, honest attitude, responsible attitude, and student cooperation.